Teologia da Libertação e volta ao fundamento - Boff, Clodovis M. (Revista Eclesiástica Brasileira, 2007)
Quer-se mostrar aqui que a Teologia da Libertação partiu bem, mas, devido à sua ambigüidade epistemológica, acabou se desencaminhando: colocou os pobres em lugar de Cristo. Dessa inversão de fundo resultou um segundo equívoco: instrumentalização da fé “para” a libertação. Erros fatais, por comprometerem os bons frutos desta oportuna teologia. Numa segunda parte, expõe-se a lógica da Conferência de Aparecida, que ajuda aquela teologia a “voltar ao fundamento”: arrancar de Cristo e, a partir daí, resgatar os pobres. Abstract: It is our intention to show here that the Theology of Liberation started off on the right track but, given its epistemological ambiguity, ended up by going astray: it put the poor in the place of Christ. A second mistake resulted from this fundamental inversion: the faith became an instrument “for” liberation. Fatal errors, for they jeopardized the good fruits of this opportune theology. In a second part, we explain the reasoning behind the Aparecida Conference: the need to help that theology to “return to basics”, to have Christ as its starting point and, through this, rescue the poor.